2016
DOI: 10.1021/acs.inorgchem.6b01326
|View full text |Cite
|
Sign up to set email alerts
|

Downscaling Effect on the Superconductivity of Pd3Bi2X2 (X = S or Se) Nanoparticles Prepared by Microwave-Assisted Polyol Synthesis

Abstract: Pd3Bi2S2 and Pd3Bi2Se2 have been successfully prepared in the form of nanoparticles with diameters of ∼50 nm by microwave-assisted modified polyol synthesis at low temperatures. The composition and morphology of the samples have been studied by means of powder X-ray diffraction as well as electron microscopy methods, including X-ray intensity mapping on the nanoscale. Superconducting properties of the as-prepared samples have been characterized by electrical resistivity measurements down to low temperatures (∼… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…The XRD pattern confirmed that our thin film crystallizes in the expected cubic crystal structure with space group I2 1 3. A Rietveld refinement of the XRD pattern gave the lattice parameters a = b = c = 8.47 Å, which are in agreement with values reported previously for bulk PBS [19][20][21]. Figure2(a-c) shows the atomic force microscope (AFM) topography image of PBS thin films.…”
supporting
confidence: 87%
See 3 more Smart Citations
“…The XRD pattern confirmed that our thin film crystallizes in the expected cubic crystal structure with space group I2 1 3. A Rietveld refinement of the XRD pattern gave the lattice parameters a = b = c = 8.47 Å, which are in agreement with values reported previously for bulk PBS [19][20][21]. Figure2(a-c) shows the atomic force microscope (AFM) topography image of PBS thin films.…”
supporting
confidence: 87%
“…21 We also observe a slope change in the sheet resistance close to 220 K seen in all films, which was not observed in bulk samples. [19][20][21] The origin of this slope change is not understood at present but we speculate that the connectivity between grains is changing with temperature, leading to a change in the conductivity of the films. To try to analyze how annealing affects the resistance of different films, we compare the residual resistivity ratio (RRR) and the residual resistivity R o in Table I.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…Moreover, the microwave-assisted polyol methodology was applied in the preparation of nanosized ternary Pd 3 Bi 2 X 2 (X = S, Se) phases (ca. 50 nm), using EG as solvent; microwave irradiation favors the dissolution of reagents, in particular in this case, elemental selenium 113. 2.2.2.…”
mentioning
confidence: 99%